State Bar of California Annual Meeting Held in Century City - Watkins, Howard::::::::: (1987)
Seated: Judy Soley, ?, and Dale Reid; Standing: Howard Watkins, Jennifer French, Howard Zidenberg, ?, Dana French, William Smith, Doris Coleman, Linda Fischbach, Herbert Levy, Donald Fischbach, Karen Kern, Richard Kern, ?, Mary Louise Frampton, Robert Oliver, Stephanie Oliver, Brad Hill, Sam Palmer III, and Melvin Richtel